Changing Perceptions and Security Challenges Related to Descendants of Immigrants in France - Vajkai, Edina Ildikó (Magyar Rendészet, 2025)
The perception of descendants of French immigrants by mainstream society and policymakers and the nature of the country’s security challenges have significantly changed in recent decades. This study explores these changes and analyses their impact on France’s social cohesion and security environment. The situation of the group concerned (who are often referred to, mistakenly, as second and third-generation immigrants) is particular since they were born in France (and, in many cases, already have French nationality). However, they often face discrimination, exclusion and social prejudice. During the research, I meticulously analysed the results of empirical studies on this topic in the French and international literature. The study is based on the comprehensive analysis of the former and actual French laws, analyses and studies, and the careful analysis of statistical data provided by the French Government. In the second half of the 20th century, immigrants typically arrived in France for economic and employment purposes, but their descendants faced a very different situation. In many cases, they start from a disadvantaged and marginalised position. In recent years, public attitudes towards the descendants of immigrants have been in transition, mainly due to the media, political discourse and current international events. Security challenges include the potential for radicalisation (which may stem from a sense of “belonging nowhere”, as in many cases they do not feel French and have few ties to their parent’s country of origin) and an increase in certain types of crime, particularly (but not exclusively) concentrated in the peripheral areas of large cities. These problems are often the result of economic and social exclusion, different educational and labour market opportunities and other (often misunderstood) cultural backgrounds.